Imaginary of female prisoners about the phenomenon of drugs - Jeane Freitas de Oliveira; Andreia Silva Rodrigues; Carlos Alberto Porcino; Maria Júlia de Oliveira Uchôa Reale (Revista Eletrônica de Enfermagem, 2016)
The involvement with drugs constitutes a main cause of women imprisonment and it is related to gender issues. A qualitative research aimed at knowing the imaginary of female prisoners about drugs. Twenty-six prisoners were investigated and projective technique of drawing-story was applied with the theme, and its analysis was grounded on the Theory of Social Representations. Elements of social representations found on drawings and story contents, permeated with realisms, showed psychic suffering and aggressiveness, objectified and anchored on participants’ affective, behavioral and psychosocial dimensions. Imprisonment makes evident the lowering of esteem, retraction and isolation signaled as motives for involvement with psychoactive substances in a trial of social recognition and overcoming of affective needs. It is concluded that participant’s imaginary of drugs elucidates subjectivities of female role in a cross-sectional phenomenon in the society, and its acknowledgement for women’s health practices is pertinent.